2021
DOI: 10.3390/jcm10184178
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Multimodal Imaging Findings in Patients with Disseminated Mycobacterium Chimaera Infection

Abstract: Background: To analyze long-term ophthalmic clinical and multimodal imaging findings of disseminated Mycobacterium (M.) chimaera infection after cardiothoracic surgery among the Swiss Cohort. Methods: Systemic and multimodal ophthalmic imaging and clinical findings including rate of recurrence were reviewed and correlated to a previously proposed classification system of choroidal lesions and classification of ocular disease. Main Outcomes Measures: long-term clinical and multimodal ocular imaging findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Zweifel et al found that choroidal lesions were hyperfluorescent on fluorescein angiography and hypofluorescent on ICG angiography, correlating with lesions seen on SD-OCT [ 7 ]. The hypofluorescence seen on ICG angiography reflects nonperfusion from active or previously active lesions [ 7 , 11 ]. The hyperfluorescence seen on fluorescein angiography correlated to choroidal thickening and retinal elevation on SD-OCT [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zweifel et al found that choroidal lesions were hyperfluorescent on fluorescein angiography and hypofluorescent on ICG angiography, correlating with lesions seen on SD-OCT [ 7 ]. The hypofluorescence seen on ICG angiography reflects nonperfusion from active or previously active lesions [ 7 , 11 ]. The hyperfluorescence seen on fluorescein angiography correlated to choroidal thickening and retinal elevation on SD-OCT [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prognosis of disseminated M. chimaera infection is poor with an estimated mortality rate of 50% [ 2 , 6 , 9 , 26 , 27 ]. Systemic complications of disseminated M. chimaera infection can include splenomegaly, cytopenia, osteomyelitis, pneumonitis, hepatitis, nephritis, skin infection, chorioretinitis, cerebral vasculitis, endocarditis, myocarditis, mediastinitis, encephalopathy, and bloodstream infection [ 2 , 10 , 11 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OCTA is able to provide quantitative microvascular information such as vessel density (VD) and vessel length density (VLD) 7 , 8 , 9 , 10 . Additionally, OCTA allows a clear and detailed visualization of retinal and choroidal microvasculature, and it is useful either for diagnostic purposes or for guiding treatment, and monitoring different retinal diseases, such as Fabryʼs disease, systemic sclerosis, optic neuritis, and infectious diseases affecting the choroid or retina 11 , 12 , 13 , 14 , 15 , 16 . Others demonstrated that VD does not change during the Valsalva maneuver in healthy young probands 17 .…”
Section: Introductionmentioning
confidence: 99%